Analisis Kebutuhan Tenaga Content Creator dalam Pengelolaan Informasi Publik (Studi Kualitatif di Dinas Ketenagakerjaan Kota Bandung) - Amelia Steffanny; Firman Yudhanegara (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of digital technology and the increasing use of social media have transformed how people access information, including public information provided by government institutions. This situation requires public organizations to manage social media more professionally by delivering informative, educational, and engaging content. This study aims to analyze the need for content creators in managing public information at the Bandung City Manpower Office. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observations, and document analysis and were analyzed using an interactive analysis model. The findings indicate that social media management involves content planning, educational and informational content production, activity documentation, editing, and content publication, all of which require specialized skills and considerable time allocation. Limited human resources and increasing workload highlight the need for dedicated content creator personnel to support effective public information management. This study emphasizes that content creators have become a strategic necessity in supporting government public communication in the digital era.